Children Thinking About Models: Analyzing a Globe - Gustafson, Brenda J.; Shanahan, Marie-Claire (Alberta Journal of Educational Research, 2011)
The purpose of this study was to explore to what extent 87 grade 5 (10-12-year-old) children, supported by instruction about scientific models, could engage in thinking beyond a naïve realist level about a globe. A qualitative framework allowed analysis of children’s responses to worksheet questions in which they identified analog-target correspondence and how models act as tools for thinking. Children’s responses were further analyzed using visual factors (Goldsmith, 1984) and interacting components (Mathewson, 2005) organized to highlight semiotic challenges associated with the models. The data demonstrated a beginning sophistication in thinking about models that for more than half the children was beyond a naïve realist level. Further research with children working with models of less familiar targets and multiple models of the same target is recommended. Cette étude avait comme objectif d’explorer dans quelle mesure 87 élèves de la 5e année (10 à 12 ans) appuyés par un enseignement sur les modèles scientifiques, pouvaient réfléchir au sujet d’un globe au-delà du niveau du réalisme naïf. Un cadre qualitatif a permis l’analyse des réponses qu’ont fournies les enfants à des questions portant sur l’identification de la correspondance analogique et les modèles en tant qu’outils de réflexion. Les réponses des élèves ont également été analysées selon des facteurs visuels (Goldsmith, 1984) et des composantes interdépendantes (Mathewson, 2005) organisées de sorte à faire ressortir les défis sémiotiques associés aux modèles. Les données ont démontré un début de réflexion sophistiquée sur les modèles qui, chez plus de la moitié des enfants, dépassait le niveau du réalisme naïf. Nous recommandons de poursuivre la recherche avec des enfants qui travaillent avec des modèles de cibles moins connues et avec plusieurs modèles de la même cible.